2022
DOI: 10.3168/jds.2021-21537
|View full text |Cite
|
Sign up to set email alerts
|

The β-casein (CSN2) A2 allelic variant alters milk protein profile and slightly worsens coagulation properties in Holstein cows

Abstract: Milk proteins genetic variants have always attracted a lot of interest as they are associated with important issues relating to milk composition and technological properties. An important debate has recently opened at an international level on the role of β-casein (β-CN) A1 and A2 polymorphisms, toward human health. For this reason, a lot of efforts has been put into the promotion of A2 milk by companies producing and selling A1-free milk, leading the farmers and breeders to switch toward A2 milk production wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 44 publications
2
18
1
1
Order By: Relevance
“…According to this, several authors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] associated the A2 milk variant with poor rennet coagulation properties. A further study [ 29 ] also found that the A1 milk genotype was associated with the best cheese-making abilities with respect to A2 milk due to a slight worsening of the coagulation properties for A2 milk.…”
Section: Physical and Technological Properties Of A2 Milkmentioning
confidence: 98%
See 4 more Smart Citations
“…According to this, several authors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] associated the A2 milk variant with poor rennet coagulation properties. A further study [ 29 ] also found that the A1 milk genotype was associated with the best cheese-making abilities with respect to A2 milk due to a slight worsening of the coagulation properties for A2 milk.…”
Section: Physical and Technological Properties Of A2 Milkmentioning
confidence: 98%
“…A recent work [ 29 ] revealed that a high proportion of consumers did not know about A2 milk, and thus had never considered purchasing this type of milk. Moreover, a positive relationship was found between socioeconomic level and A2 milk awareness [ 30 ].…”
Section: The A2 Milk Marketmentioning
confidence: 99%
See 3 more Smart Citations